Design and skid resistance evaluation of skeleton-dense epoxy asphalt mixture for steel bridge deck pavement. (1st July 2016) - Qian, Zhen-dong; Liu, Yang; Liu, Chang-bo; Zheng, Dong
Highlights: One skeleton-dense epoxy asphalt mixture was designed and evaluated. The designed mixture meets the operating requirements of steel bridge pavement. The designed mixture has superior rutting resistance and anti-fatigue performance. The designed mixture could significantly improve the pavement skid-resistance. Abstract: To improve the skid-resistance of epoxy asphalt concrete pavement for the steel bridge deck, an epoxy asphalt mixture with skeleton-dense structure was proposed. This paper carries out a laboratory study on the design and performance evaluation of skeleton-dense epoxy asphalt mixture. Firstly, the mixture was designed through a volume design method, and the pavement performance was investigated to evaluate the applicability of the skeleton-dense epoxy asphalt mixture for the steel bridge pavement. Secondly, the skid-resistance of the skeleton-dense epoxy asphalt mixture was evaluated, including the initial skid-resistance, long-term skid-resistance and skid-resistance under the inclement weather condition. The long-term skid-resistance attenuation law was simulated by the small traffic load simulation system MMLS3, and the skid-resistance life was predicted. The skid-resistance attenuation law under the rainy and freezing weather was investigated in the laboratory, and the influence of water film thickness, different ice situations on the pavement skid-resistance was analyzed. Finally, gray correlation analysis method was applied to the comprehensive evaluation of pavement skid-resistance. Results indicate that the proposed mixture could meet the operating requirements of steel bridge pavement and dramatically improve the skid-resistance of epoxy asphalt concrete pavement.